Digital Marketing & Digital Entrepreneurship During Social Restriction Policy in Indonesia - Hery Margono (International Journal of Artificial Intelligence Research, 2022)
Although marketing and entrepreneurship are not new concepts, in times of social restrictions due to the pandemic generated by Covid 19, which has limited at least half of the world's population, marketing and entrepreneurship, such as MSMEs, have been significantly impacted. The intensity of consumers and the declining flow of goods and services resulted in a reduction in the income of business actors and a decrease in the flow of goods and services traded. This study discusses marketing and entrepreneurship in the era of social restriction policies. The research methodology uses a qualitative approach with a descriptive method. The results of the study show that the decline in marketing as a result of COVID-19 has caused entrepreneurs who are generally SMEs to transform into digital entrepreneurs by adopting digital technology and digital marketing. . However, in this study, the authors also found that the process of transformation into a digital entrepreneur cannot be done without the support of the government through the promotion of digitalization of the entrepreneurial sector such as the entrepreneurship sector. In general, the conclusion from the entrepreneurial side is that businesses must grow according to consumer needs, namely where they want to go and under any conditions. This is where the need to transform marketing and entrepreneurship into digital entrepreneurship and digital marketing.